2023
DOI: 10.3390/ph16091297
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Longitudinal Strain to Assess Cancer Therapy-Related Cardiac Dysfunction and Immune Checkpoint Inhibitor-Induced Myocarditis

Yudai Tamura,
Yuichi Tamura

Abstract: Longitudinal strain (LS) measured by echocardiography has been reported to be useful not only for the diagnosis and risk stratification of various cardiac diseases, but also in cardio-oncology. Most previous studies have been conducted on patients undergoing treatment with anthracyclines and human epidermal growth factor receptor 2-targeted therapies. Existing guidelines recommend that global LS (GLS) should be measured before and after the administration of cancer drugs. This recommendation is based on many r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…It predicts heart failure with preserved ejection fraction and other adverse outcomes, 6 aiding in assessing dysfunction severity, guiding treatment and monitoring therapeutic response. 7 Our study has overcome the common pitfalls of the technique.…”
Section: Discussionmentioning
confidence: 91%
“…It predicts heart failure with preserved ejection fraction and other adverse outcomes, 6 aiding in assessing dysfunction severity, guiding treatment and monitoring therapeutic response. 7 Our study has overcome the common pitfalls of the technique.…”
Section: Discussionmentioning
confidence: 91%
“…However, there are no specific indications for patients treated with ICIs. Several studies demonstrated the utility of GLS to predict subclinical cardiac toxicities also in patients treated with ICIs [19,20]. A recent retrospective analysis compared GLS values between patients who developed ICI-myocarditis and those without adverse events, and demonstrated that GLS was reduced only among patients who developed myocarditis; furthermore, GLS was reduced either in patients presenting with a reduced LVEF and in those with a preserved LVEF.…”
Section: Diagnostic Testing For Ici-associated Myocarditismentioning
confidence: 99%